Effects and side effects of measures to attract firms - a micro-simulation study of firm location choice. - Bodenmann, Balz R.; Axhausen, Kay W. (Routledge, 2012)
This paper investigates the effects of different possible options for cantonal and municipal authorities' intent on attracting firms: improvements in transport infrastructure, designation of new building zones, and tax reductions. These options have been tested by simulating the location decisions of existing firms. The parameters for these simulations have been estimated with a discrete choice model using data from the commercial registers of the Canton of St. Gallen and the two Appenzell cantons (Innerrhoden and Ausserrhoden) covering the years 1991 to 2006. The aim of this paper is not only to show the effects, but also to detect potential negative side effects. The simulation results show that tax reductions have an unparalleled large effect, meaning positive effects in the municipalities concerned as well as negative side effects in adjacent municipalities. Generally, effects are more intense in regions with a large number of firms already present. Interestingly, due to large positive effects in a specific region, negative side effects can also be identified over long distances in other regions. Cities and towns are especially affected by these long-distance effects.
Keywords: Wirtschaftsentwicklung; Wirtschaftsförderung; Standort; Wirkungsanalyse; Simulation; Wirtschaftspolitik; Förderungspolitik; Unternehmensförderung